Development of The Welfare Index at Sub-district Level in West Java 2020: A Small Area Estimation Approach - Nimas Ezra Monadiyan; Faisal Haris (Politeknik Statistika STIS, 2021)
Welfare as an alternative measure for poverty, is an important indicator to measure. But there is no composite indicator that specifically measures the prosperity of a population yet. Considering the increase of data needed and the lack of available data at the smaller level, this study develops the Welfare Index at sub-district level for West Java in 2020 using a small area estimation approach to explain the condition of welfare of the population. The indicators in sub-district level formed in this study were created from two kinds of data. The first type of indicators were formed from SUSENAS using Small Area Estimation and the other type of indicators were formed from PODES aggregation. All the indicators were then processed with factor analysis to form the Welfare Index. The Welfare Index formed shows the range of 22.86 to 83.76 and generally higher in the northern part of West Java. This index has a correlation of 0.798 with the Human Development Index because of the components that defined both indexes. The existence of this correlation shows that the Welfare Index formed is able to explain the conditions/phenomena being measured.